2022
DOI: 10.3390/ma15196599
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Mechanical Properties of High-Volume Fly Ash Concrete with Nano-Silica and Silica Fume

Abstract: This study investigated the effects of nano-silica (NS) and silica fume (SF) on the hydration reaction of high-volume fly ash cement (HVFC) composites. In order to solve the dispersibility problem caused by the agglomeration of NS powder, NS and NSF solutions were prepared. NS content and SF content were used as main variables, and an HVFC paste was prepared in which 50% of the cement volume was replaced by fly ash (FA). The initial heat of hydration was measured using isothermal calorimetry to analyze the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…The results indicated that concrete with a low water–binder ratio possessed a dense internal structure, lower calcium hydroxide content, and a less conspicuous carbonation effect. However, after 14 and 28 days of rapid carbonisation, an increase in SF content led first to an increase and then a decrease in the carbonation depth [ 39 , 40 ]. Specifically, the carbonation depth of concrete containing 7% SF was reduced by 10.1% and 12.3% at 14 and 28 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that concrete with a low water–binder ratio possessed a dense internal structure, lower calcium hydroxide content, and a less conspicuous carbonation effect. However, after 14 and 28 days of rapid carbonisation, an increase in SF content led first to an increase and then a decrease in the carbonation depth [ 39 , 40 ]. Specifically, the carbonation depth of concrete containing 7% SF was reduced by 10.1% and 12.3% at 14 and 28 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It can replace 5-10% of the cement. Silica fume increases the strength and durability of concrete, but it can reduce workability and accelerate the setting, which can reduce the time required to initiate formwork stripping [123].…”
Section: Silica Fumementioning
confidence: 99%
“…The filling ability and the pozzolanic reaction of silica fume could effectively improve the mechanical properties of rubberised concrete. However, different optimum proportions of silica fume have been reported in previous studies [40,44,52] and [45][46][47]. Thus, it is imperative to conduct a comprehensive experimental study to evaluate the mechanical and thermal properties of rubberised concrete produced using different proportions of rubber powder and silica fume.…”
Section: Research Significancementioning
confidence: 99%
“…Extensive research reported that replacing OPC with silica fume increases the packing density and densifies the interfacial transition zone between rubber particles (crumbs and chips), aggregates, and OPC matrix, leading to better bonding and, thus, enhancing the strengths of rubberised concrete [40][41][42]. The typical silica fume content adopted in previous studies was 10% as the OPC replacement [40,43,44], while other research adopted different silica fume contents [45][46][47]. Furthermore, the optimum content of silica fume depends on the OPC content and water-cement ratio [48].…”
Section: Introductionmentioning
confidence: 99%